Paradoxical reactions in Buruli ulcer after initiation of antibiotic therapy: Relationship to bacterial load - Frimpong, Michael; Agbavor, Bernadette; Duah, Mabel Sarpong; Loglo, Aloysius; Sarpong, Francisca N.; Boakye-Appiah, Justice; Abass, Kabiru M.; Dongyele, Mathias; Amofa, George; Tuah, Wilson; Frempong, Margaret; Amoako, Yaw A.; et al. (PLOS Neglected Tropical Diseases, 2019)
Author summary Buruli ulcer is a neglected tropical skin disease caused by the third most common pathogenic mycobacterium: Mycobacterium ulcerans. Paradoxical reaction, a phenomenon observed in some patients is characterised by worsening of existing lesion(s) with attendant pain and occurrence of new lesions during or after antibiotic therapy following an initial period of clinical improvement. This significantly affects treatment outcomes. In this clinical study, tissue samples obtained from patients were subjected to 16S rRNA/ IS2404 qPCR to measure bacterial load. This was to identify a link between bacterial load in BU lesions and the development of paradoxical reactions following initiation of antibiotic treatment. We found that 13% of participants developed PR. Patients who developed PR had higher baseline bacterial load; a higher rate of positive M. ulcerans culture and persistently positive culture during antibiotic treatment. Occurrence of a paradoxical reaction was associated with delayed healing.